An examination of the relationships between professional quality of life, adverse childhood experiences, resilience, and work environment in a sample of human service providers. (October 2015) - Hiles Howard, Amanda R.; Parris, Sheri; Hall, Jordan S.; Call, Casey D.; Razuri, Erin Becker; Purvis, Karyn B.; Cross, David R.
Abstract: The current study investigated the relationship between ACEs, resilience, and work environment and professional quality of life including compassion satisfaction, burnout, and secondary trauma stress among a group of child welfare professionals working with children in the foster care system. Participants were 192 professionals representing 48 organizations providing a range of services for children residing in foster care within a large metropolitan area in the southern USA. Data showed that professionals had more ACEs than the norm sample (4 or more ACEs: 25.1% v. 12.5%). However, contrary to our hypotheses, regression analysis revealed that individuals with more ACEs had higher compassion satisfaction and lower rates of burnout. Moreover, number of ACEs was not significantly related to secondary traumatic stress. The variables found most predictive of poor professional quality of life were low levels of resilience and controlling organizational leadership. Ways to improve professional quality of life amid human service professionals and practical implications of these findings are discussed. Highlights: The relationship between ACES, resilience, and work environment and ProQOL among human service professionals was examined. Individuals with more ACEs had higher ProQOL. Poor ProQOL was predicted by low resilience and controlling leadership.